Interdependence of right and left hands in sight-read, written, and rehearsed fingerings of parallel melodic piano music - Parncutt, R; Sloboda, J; Clarke, E (Taylor and Francis, 1999)
In an exploratory study of interactions between left hand (LH) and right hand (RH) fingerings, 6 professional pianists performed two Czerny studies in which LH and RH negotiate identical isochronous melodic material separated by one octave. Participants performed at sight and following rehearsal, with RH alone and hands together. Performances were recorded as MIDI data and as birds-eye video of the hands. Fingerings were transcribed from (slow motion) video recordings. Pianists wrote (optimal or intended) fingerings on scores during rehearsal. Intended LH fingerings were disrupted by hands-together performances more than intended RH fingerings, and RH fingerings involved more or bigger stretches between fingers than LH fingerings. Both findings are consistent with the intuition that pianists focus more attention on RH than LH fingerings in parallel melodic passages. Possible reasons include the difficulty of dividing attention between the hands, differences between the technical skill of the hands in fast melodic passages, and the greater perceptual salience of RH errors.